Henry's clinical diagnosis and management by laboratory methods - McPherson, Richard A. ;Pincus, Matthew R. (St. Louis, Missouri : Elsevier Science, 2017)
Recognized as the definitive reference in laboratory medicine since 1908, Henry's Clinical Diagnosis continues to offer state-of-the-art guidance on the scientific foundation and clinical application of today's complete range of laboratory tests. Employing a multidisciplinary approach, it presents the newest information available in the field, including new developments in technologies and the automation platforms on which measurements are performed.
General concepts and administrative issues -- Optimizing laboratory workflow and performance -- Preanalysis -- Analysis : principles of instrumentation -- Analysis : clinical laboratory automation -- Point-of-care testing and physician office laboratories -- Postanalysis : medical decision making -- Interpreting laboratory results -- Laboratory statistics -- Quality control -- Clinical laboratory informatics -- Financial management -- Biological, chemical, and nuclear terrorism : role of the laboratory -- Evaluation of renal function, water, electrolytes, and acid-base balance -- Biochemical markers of bone metabolism -- Carbohydrates -- Lipids and dyslipoproteinemia -- Cardiac injury, atherosclerosis, and thrombotic disease -- Specific proteins -- Clinical enzymology -- Evaluation of liver function -- Laboratory diagnosis of gastrointestinal and pancreatic disorders -- Toxicology and therapeutic drug monitoring -- Evaluation of endocrine function -- Reproductive function and pregnancy -- Vitamins and trace elements -- Chemical basis for analyte assays and common interferences -- Basic examination of urine -- Cerebrospinal, synovial, serous body fluids, and alternative specimens -- Basic examination of blood and bone marrow -- Hematopoiesis -- Erythrocytic disorders -- Leukocytic disorders -- The flow cytometric evaluation of hematopoietic neoplasia -- Immunohematology -- Transfusion medicine -- Hemapheresis -- Tissue banking and progenitor cells -- Coagulation and fibrinolysis -- Platelet disorders and von Willebrand disease -- Laboratory approach to thrombotic risk -- Antithrombotic therapy -- Overview of the immune system and immunologic disorders -- Immunoassays and immunochemistry -- Laboratory evaluation of the cellular immune system -- Laboratory evaluation of immunoglobulin function and humoral immunity -- Mediators of inflammation : complement, cytokines, and adhesion molecules -- Mediators of inflammation : cytokines and adhesion molecules -- Human leukocyte antigen : the major histocompatibility complex of man -- The major histocompatibility complex and disease -- Immunodeficiency disorders -- Clinical and laboratory evaluation of systemic rheumatic diseases -- Vasculitis -- Organ-specific autoimmune diseases -- Allergic diseases -- Viral infections -- Chlamydial, rickettsial, and mycoplasmal infections -- Medical bacteriology -- In vitro testing of antimicrobial agents -- Spirochete infections -- Mycobacteria -- Mycotic diseases -- Specimen collection and handling for diagnosis of infectious diseases -- Introduction to molecular pathology -- Molecular diagnostics : basic principles and techniques -- Polymerase chain reaction and other nucleic acid amplification technology -- Hybridization array technologies -- Applications of cytogenetics in modern pathology -- Establishing a molecular diagnostics laboratory -- Molecular diagnosis of genetic diseases -- Identity analysis : use of DNA analysis in parentage, forensic, and missing persons testing -- Pharmacogenomics and personalized medicine -- Diagnosis and management of cancer using serologic and other body fluid markers -- Oncoproteins and early tumor detection -- Molecular diagnosis of hematopoietic neoplasms -- Molecular genetic pathology of solid tumors -- High-throughput genomic and proteomic technologies in the postgenomic era -- Physiologic solutions, buffers, acid-base indicators, standard reference materials, and temperature conversions -- Desirable weights, body surface area, and body mass index -- Approximations of total blood volume -- Periodic table of the elements -- SI units -- Common chimeric genes identified in human malignancies -- Disease/organ panels -- Guidelines for ordering blood for elective surgery.
Revision of: Henry's clinical diagnosis and management by laboratory methods / [edited by] Richard A. McPherson, Matthew R. Pincus. 22nd edition. ©2011.
Includes bibliographical references.
Keywords: DIAGNOSIS, LABORATORY